-5x+7x-8=2(x-5)-3

Simple and best practice solution for -5x+7x-8=2(x-5)-3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -5x+7x-8=2(x-5)-3 equation:



-5x+7x-8=2(x-5)-3
We move all terms to the left:
-5x+7x-8-(2(x-5)-3)=0
We add all the numbers together, and all the variables
2x-(2(x-5)-3)-8=0
We calculate terms in parentheses: -(2(x-5)-3), so:
2(x-5)-3
We multiply parentheses
2x-10-3
We add all the numbers together, and all the variables
2x-13
Back to the equation:
-(2x-13)
We get rid of parentheses
2x-2x+13-8=0
We add all the numbers together, and all the variables
5!=0
There is no solution for this equation

See similar equations:

| 4x2+3x2= | | 90/x-2+3=x | | 6x-10=10x+x | | -6(v+3)+2v+7=6v+8 | | 26x²-8=0 | | 12-5*6^x=2 | | -9(v+2)+4v+7=7v+6 | | -6(x+2)=2x+7=7x+6 | | 4x–3=8x–19 | | 10n+5=3n-2 | | 3/8×-1/3×+6=1/6x | | x-4)(x-10)=0 | | 16–5x=4x+2 | | 15+3x=31+x | | (3x-7)/(x+5)=0 | | 15x+3x=31+x | | -4/v=-6 | | 5x-3=3x+24 | | x/5-20=50 | | 45(x+1)=3(x+2)+11 | | x/8-12=-24 | | -101.01=-9.1x | | x=21/25 | | 0.5x/10000=0.5x(x-8000)/5000 | | 8(7x-7)=55 | | 9+x2=25 | | X^2+6x=7.84 | | 15x-4=14-3x | | y/2+y/3+y/4=14 | | (8w-9)(4w-9)=0 | | 11n-5n=6 | | 7x+5=40* |

Equations solver categories